Design and implementation of an autonomous multistoried car parking system with human machine interface (HMI) controlled by programmable logic controller (PLG) - Ho, Siang Ven (2013)
With the vast growth in economy of a developing country such as Malaysia, the trend of purchasing new vehicle is seen common in the society. This indirectly causes traffic congestions especially in large towns and cities such as Kuala Lumpur and Penang Island. A typical conventional car parking facility was intended to reduce parking spaces but the parking process is somehow time consuming, where the patron has to spend time searching for empty parking lot and hence petrol consuming and environment unfriendly.In order to alleviate the problems as mentioned, an automated multistoried car parking system has been implemented whereby it helps in minimizing parking area compared to the conventional car parking facilities. In this project a prototype of an automated car parking system based on programmable logic controller (PLC) will be developed in identifying the available parking spaces in the car parking facility, access parking and retrieval process without any help of any human personnel. This project mainly concerns about the entire operating procedure of the autonomous multistoried car parking system as well as its building architecture together with electrical and mechanical system design including software and hardware design for ideas of vehicle lifting and retrieving, which serve in reducing the period of time needed and centralize parking orientation and automation.